Human Herpesvirus 6 Reactivation: A Rare Case of Acute Liver Failure and Literature Review - Wozniak, Hannah; Vionnet, Jeanne-Laure; Schibler, Manuel; Heidegger, Claudia Paula; Pugin, Jérôme; Spahr, Laurent; Cereghetti, Sara (Archives of Clinical and Medical Case Reports, 2023)
Acute hepatitis is a frequent cause of admission to intensive care unit (ICU). The differential diagnosis is broad and determining the etiology can be challenging. We report a 68-year-old immunocompromised patient who developed acute liver failure associated with pericardial effusion who was diagnosed with human herpesvirus 6 (HHV-6) reactivation. The diagnosis was made by a positive real-time PCR (rPCR). After an extensive hepatitis workup with viral, toxic and autoimmune investigations and after exclusion of an inherited chromosomally integrated HHV-6 by rPCR of the fingernails, no convincing alternative diagnosis was found. The evolution of transaminases and viremia monitoring by quantitative PCR under antiviral treatment is described. Although HHV-6 reactivation is a very rare cause of acute hepatitis and is difficult to diagnose, fulminant hepatitis is one of the most common complications of HHV-6 reactivation. Since acute liver failure can lead to specific medical interventions, to liver transplantation, or can be fatal, the diagnosis of HHV-6 should be systematically considered, and early detection can lead to a better prognosis.